Perancangan Media Promosi Rumah Gadang Mande Rubiah Dalam Bentuk Audio Visual - Fitri Ramadhany; Muhammad Rio Akbar; Vernanda Em Afdhal (fakultas Desain Koomunikasi visual, 2021)
This design was designed with the aim of introducing cultural heritage located in the Lunang District, Pesisir Selatan. So that in the future more people will visit with the aim of knowing more about the history that is in it. The media used is more effective in packaging the information conveyed. Furthermore, it will be analyzed using SWOT analysis theory. This is done for a creative approach in reaching the target audience and the goals and messages contained in it can be conveyed properly and precisely. Then make the concept of strategies and creative programs that really provide solutions in solving problems in design. The design process produces a promotional video for Rumah Gadang Mande Rubiah. This promotional video is the main media that has an attractive visual element, and a visual message that contains information about the promotional video for Rumah Gadang Mande Rubiah. The results of the design can later be used by Rumah Gadang Mande Rubiah as a way to introduce it to the wider community.